1988
DOI: 10.1017/s0021859600083180
|View full text |Cite
|
Sign up to set email alerts
|

The response of field beans (Vicia fabaL.) to irrigation and sowing date. 2. Growth and development in relation to yield

Abstract: S U M M A R YThe growth and yield of four crops of field bean cv. Maris Bead in response to irrigation and sowing date were analysed in relation to leaf area expansion and senescence and their absorption and utilization of photosynthetically active radiation (PAR). Total dry matter (D.M.) production and seed yield were strongly correlated with total green area duration (GAD) and post-flowering GAD respectively.Total D.M. production was also strongly related to radiation absorbed by the green surfaces of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 69 publications
4
15
0
3
Order By: Relevance
“…This has also been reported by Wallace et al (1995) in navy beans and Husain et al (1988b) in field beans. Wallace et al (1995) observed that the rate of development of dry beans was largely controlled by temperature, accounting for 80% of the variation.…”
Section: Phenologysupporting
confidence: 85%
See 1 more Smart Citation
“…This has also been reported by Wallace et al (1995) in navy beans and Husain et al (1988b) in field beans. Wallace et al (1995) observed that the rate of development of dry beans was largely controlled by temperature, accounting for 80% of the variation.…”
Section: Phenologysupporting
confidence: 85%
“…The linear relationship between the development rate of the phases (especially during E-F and S-H) and mean temperature has also been reported in dry beans (Wallace et al 1995), common beans (P. vulgaris L.; Summerfield et al 1991), and field beans (Husain et al 1988b). It suggests that the development rate of pinto beans did not respond to photoperiod.…”
Section: Phenologymentioning
confidence: 56%
“…The very low LAI (2.2, below the critical LAI) in combination with a low total intercepted PAR in shaded unirrigated plants gave the lowest TDM among all the treatments. Increased DM production with increased radiation interception has been reported in chickpeas (Hernandez 1986), lentils (McKenzie & Hill 1991), peas (Heath et al 1994), field bean (Husain et al 1988), and mung beans (Liyanage & Me William 1981). Virtually all of the effects of these treatments on DM production are the result of reduced radiation interception and not to reduced efficiency of production of DM from intercepted radiation.…”
Section: Dry Matter Productionmentioning
confidence: 96%
“…Previous work on grain legumes in Canterbury has shown that growth and development of lentils (Lens culinaris L.) McKenzie & Hill (1991) and faba beans (Viciafaba L.) (Husain et al 1988) was related to radiation interception and that radiation use efficiency was more stable than radiation interception. In legumes one of the main determinants of yield is harvest index, which is much less stable than in cereals.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of dry matter accumulated by a wide range of crops, including apples and sugarbeet (Monteith 1977), barley (Gallagher & Biscoe 1978), field beans (Hussain et al 1988), lentil (McKenzie & Hill 1991), and potatoes (Allen & Scott 1980) has been related to the amount of intercepted photosynthetically active radiation (RI). The relationship is linear with the slope of the line being the radiation use efficiency (RUE).…”
Section: Introductionmentioning
confidence: 99%